PENERAPAN MATEMATIKA PADA ILMU EKONOMI : FUNGSI LINIER PADA PAJAK DAN SUBSIDI - Rahmatullah Nasution, Armanda Riddwan Alif; Sky Aldiansyah, Glem Alin; Faisal Farhan, Muhammad; Syarifuddin, Muhammad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
A linear function is a function used to calculate the number of terms of a series that changes constantly. The problem found is the obstacles experienced by students in understanding the linear function sub-material on taxes. The purpose of writing this article is to identify the problems experienced by students and develop recommendations to improve effectiveness in learning. The method used is literature review. The results of the study The application of the Linear Equation system can help calculate the burden of supply and producers who usually charge the tax burden to buyers/consumers. The linear system can determine the selling price of products that have increased compared to before taxes and affect product demand in the market. Subsidies will change the supply function and market equilibrium. The imposition of a tax on a type of good will result in its price becoming more expensive, so the supply curve will shift to the upper left, resulting in a new market equilibrium.